Dynamin-2 Function and Dysfunction Along the Secretory Pathway - González-Jamett, Arlek M.; Momboisse, Fanny; Haro-Acuña, Valentina; Bevilacqua, Jorge A.; Caviedes, Pablo; Cárdenas, Ana M. (Frontiers in Endocrinology, 2013)
Dynamin-2 is a ubiquitously expressed mechano-GTPase involved in different stages of the secretory pathway. Its most well-known function relates to the scission of nascent vesicles from the plasma membrane during endocytosis; however, it also participates in the formation of new vesicles from the Golgi network, vesicle trafficking, fusion processes and in the regulation of microtubule, and actin cytoskeleton dynamics. Over the last 8 years, more than 20 mutations in the dynamin-2 gene have been associated to two hereditary neuromuscular disorders: Charcot–Marie–Tooth neuropathy and centronuclear myopathy. Most of these mutations are grouped in the pleckstrin homology domain; however, there are no common mutations associated with both disorders, suggesting that they differently impact on dynamin-2 function in diverse tissues. In this review, we discuss the impact of these disease-related mutations on dynamin-2 function during vesicle trafficking and endocytotic processes.